Multinational corporate social policy process for ethical responsibility in sub-Saharan Africa - Pratt, Cornelius B. (Journal of business ethics, 1991)
The article identifies the challenges that multinational corporations (MNCs) from the developed world face in sub-Saharan Africa and examines the direct foreign-investment and development interests of the region. In light of these challenges and interests, it also explores answers to the question “What is to be done?”, The occurrence of MNCs' operations in culturally pluralistic societies suggest that they use, as the basis for a corporation-formulated regional code of conduct, a value-based corporate social policy process. That process should embody utilitarian and situation ethics in the exercise of MNCs' prima facie operations and of their responsibilities to society. For the African normative environment, the appeal of this approach is substantiated by the notion that both utilitarian and situation ethics are at once consistent with the region's investment codes, development interests, and value systems. But more than that, utilitarian and situation ethics are consistent with corporate social policy process and can assist MNCs to meet effectively their social responsibilities by helping them reverse the economic stagnation of most of the continent., However, because deontological (that is, Kantian) ethics emphasize autonomous actions that satisfy individual goals, they are largely at odds with sub-Saharan African value systems that typically emphasize the ethnic group (heteronomy) rather than the self. MNCs would, therefore, do well to de-emphasize their use in the region.